Highly sensitive ion-exchanger based polyvinyl chloride membrane sensor for determination of vinpocetine and its use in drugs analysis - Salih, Faisal Abdula; Novakovskii, Andrei D.; Zaitseva, Yulia G.; Egorov, Vladimir V. (Journal of the Belarusian State University. Chemistry, 2024)
It has been established that the correct choice of the ion-exchanger, plasticiser and the measurement conditions makes it possible to achieve analytical characteristics of vinpocetine-sensitive electrodes based on commercially available components, far superior to those described in the literature. It has been found, that the effect of pH on the vinpocetine-sensitive electrodes response takes place in much more acidic media than might be expected from protolytic equilibrium and is due to the extraction of the molecular form of vinpocetine into the membrane phase from both external and inner solutions. Very good parameters of selectivity (from –7.4 to – 9.8 in respect to inorganic ions), lower detection limit (1.7 ⋅ 10–7 mol ⋅ L–1), linear response range (1.0 ⋅ 10– 6 mol ⋅ L–1), and potential reproducibility (± 0.06 mV in 1.0 ⋅ 10– 4 mol ⋅ L–1 solution of vinpocetine) are achieved using 2-nitrophenyl octyl ether as a plasticiser, potassium tetrakis(4-chlorophenyl)borate as an ion-exchanger and creating conditions that exclude non-exchangable extraction of vinpocetine into the membrane at the stages of both conditioning the electrode and performing measurements. Methods for the determination of vinpocetine in dosage forms (pills and solutions for injections) using both direct potentiometry and potentiometric titration techniques characterised by simplicity, rapidity and high metrological characteristics have been proposed.
Keywords: potentiometry; ion-selective electrode; vinpocetine; lipophilic physiologically active amines; pharmaceutical analysis